The Influence of the Types of Iraqi Sands on the Physical and Mechanical Properties of Foamed Concrete - Al-Abbasi, Mohammed Salih; Al-Mulali, Mohammed Zuhear (Engineering, Technology & Applied Science Research, 2025)
Recently, the use of foamed concrete has expanded significantly in Iraq due to its properties and the availability of raw materials. Since fine aggregate (sand) is one of the basic elements in the production of foamed concrete, it plays an important role in determining its properties. This study examined three types of sand (S1, S2, S3), distributed across three governorates (Karbala, Salah al-Din, and Anbar), respectively. Numerous rigorous tests were conducted on this sand to determine its physical and chemical properties. The results showed a significant improvement in the physical properties of the concrete during the test period, related to the dry density and porosity, which are related to the speed of transmission of ultrasonic waves through the concrete medium. There was also a significant improvement in mechanical properties, including compressive, tensile, and flexural strengths during the test. The results also indicate that the best type of sand was Anbar sand (S3) used in the MS3 concrete mix.